2017
DOI: 10.1007/s00412-017-0653-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatial organization of chromosome territories in the interphase nucleus of trisomy 21 cells

Abstract: In the interphase cell nucleus, chromosomes adopt a conserved and non-random arrangement in subnuclear domains called chromosome territories (CTs). Whereas chromosome translocation can affect CT organization in tumor cell nuclei, little is known about how aneuploidies can impact CT organization. Here, we performed 3D-FISH on control and trisomic 21 nuclei to track the patterning of chromosome territories, focusing on the radial distribution of trisomic HSA21 as well as 11 disomic chromosomes. We have establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 69 publications
4
8
0
Order By: Relevance
“…However, changes in the radial position of CTs and individual gene loci can occur in a variety of physiological conditions, including cell differentiation (Kuroda et al, 2004;Stadler et al, 2004;Marella et al, 2009a;Sehgal et al, 2016;Orsztynowicz et al, 2017), gametogenesis (Scherthan et al, 1998;Mudrak et al, 2009), signaling in response to extra-cellular stimuli (Branco et al, 2008;Mehta et al, 2010;Mourad et al, 2014;Ioannou et al, 2015), as well as following DNA damage (Spitkovsky et al, 2002;Mehta et al, 2013;Schwarz-Finsterle et al, 2013;Kulashreshtha et al, 2016). Importantly, the radial placement of CTs in the nucleus is often altered in cancer cells Murata et al, 2007;Marella et al, 2009b;Timme et al, 2011) and in the presence of chromosomal translocations and aneuploidies associated with cancer (Taslerová et al, 2003;Taslerová et al, 2006;Harewood et al, 2010;Allinne et al, 2014) or congenital disorders (Jowhar et al, 2018b;Kemeny et al, 2018). Altogether, these findings suggest that the non-random radial arrangement of chromosomes and sub-chromosomal regions with respect to the nuclear lamina is a universal feature of nuclear architecture, which is conserved across species and whose alteration is associated with a variety of disease conditions.…”
Section: Radial Arrangement Of Chromosomesmentioning
confidence: 99%
“…However, changes in the radial position of CTs and individual gene loci can occur in a variety of physiological conditions, including cell differentiation (Kuroda et al, 2004;Stadler et al, 2004;Marella et al, 2009a;Sehgal et al, 2016;Orsztynowicz et al, 2017), gametogenesis (Scherthan et al, 1998;Mudrak et al, 2009), signaling in response to extra-cellular stimuli (Branco et al, 2008;Mehta et al, 2010;Mourad et al, 2014;Ioannou et al, 2015), as well as following DNA damage (Spitkovsky et al, 2002;Mehta et al, 2013;Schwarz-Finsterle et al, 2013;Kulashreshtha et al, 2016). Importantly, the radial placement of CTs in the nucleus is often altered in cancer cells Murata et al, 2007;Marella et al, 2009b;Timme et al, 2011) and in the presence of chromosomal translocations and aneuploidies associated with cancer (Taslerová et al, 2003;Taslerová et al, 2006;Harewood et al, 2010;Allinne et al, 2014) or congenital disorders (Jowhar et al, 2018b;Kemeny et al, 2018). Altogether, these findings suggest that the non-random radial arrangement of chromosomes and sub-chromosomal regions with respect to the nuclear lamina is a universal feature of nuclear architecture, which is conserved across species and whose alteration is associated with a variety of disease conditions.…”
Section: Radial Arrangement Of Chromosomesmentioning
confidence: 99%
“…To this aim, more automated methods are needed and efficient 3D segmentation is required to delimit the boundary of objects such as the nucleus or its chromatin organization [ 19 ]. Investigation of the cell nucleus has strongly benefited from these applications, as the nucleus is a spatial structure for which morphology can be modified in diseases [ 20 , 21 ]. Segmentation applied to nuclear organization is also a research tool to investigate the genetic determinants of nuclear size and shape and also chromatin organization [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Within NucleusJ 1.0, segmentation methods to compute nuclear morphology (a modified Otsu threshold method) and chromatin organization (a 3D watershed method) were chosen as the most relevant methods for nuclear segmentation for 3D nuclei. Although initially developed for plant nuclei stained with DNA dyes [ 23 , 28 , 29 ], NucleusJ 1.0 can also be used for other cell types [ 20 ] and adapted to segment Fluorescence in situ hybridization (FISH) signals [ 29 ]. However, each NucleusJ 1.0 analysis is time-consuming, the segmentation threshold is user-dependent and nuclear segmentation failed for a substantial fraction of nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using fluorescence in situ hybridization (FISH) and immunostaining have revealed that territorial chromosomes have intermingling regions, which are enriched for transcription markers and exhibit high transcriptional activity 13,14 . In addition, spatial repositioning of chromosomal territories in human cells can occur during the DNA damage response and in aneuploid cells, and altered chromosomal territories are associated with human cancers 12,[15][16][17] . The radial arrangement of chromosomes and interchromosomal communication appear to be critical for diverse cellular responses and for maintaining genome integrity.…”
Section: Global Genome Configuration In the Interphase Nucleusmentioning
confidence: 99%